Managerial Adaptation Strategies in Managing Multigenerational Conflicts in the Workplace: Dynamics, Challenges, and the Transformation of Modern HRM Practices - Titin; Sulaeman, Moh Muklis; Wibowo, Sandi Nasrudin; Nurcholidah, Lilik; Cahyono, Puguh (PT. LITERASI SAINS NUSANTARA, 2025)
The phenomenon of generational diversity in today’s workforce has created complex social dynamics that often lead to conflicts affecting organizational effectiveness. This study aims to explore in depth the managerial adaptation strategies employed to address and manage multigenerational conflicts in the workplace by examining the dynamics, challenges, and transformational practices in modern human resource management (HRM). A qualitative approach is applied using a literature review method and descriptive analysis of 21 selected scholarly articles published between 2010 and 2024, sourced from Google Scholar and other credible academic platforms. The study reveals that managerial approaches grounded in leadership flexibility, intergenerational understanding, effective communication, and the strengthening of inclusive organizational cultures are crucial in reducing conflicts and fostering intergenerational collaboration. The integration of theories such as Situational Leadership, Conflict Management, Social Exchange, and Diversity Management reinforces the critical role of managers in transforming conflict into opportunities for team performance development. Case studies from several Indonesian organizations, including PT Telkom Indonesia and Bank BCA, demonstrate that adaptive strategies can significantly enhance productivity, employee retention, and cross-generational innovation. This research offers a conceptual contribution to the development of modern HRM literature and provides practical guidance for organizations in designing work policies that are responsive to generational diversity.